TRADISI TIBA MEKA WERU SEBAGAI SOLIDARITAS MAHASISWA MANGGARAI DI KOTA MALANG - Bonifasia Yesivina Inda; Winin Maulidya Saffanah (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
The Tiba Meka Weru tradition is a traditional ceremony for welcoming guests carried out by the people of Manggarai, East Nusa Tenggara. This tradition aims to welcome important guests, such as government figures, community leaders and religious figures, with full respect and familiarity. The aim of the research on the Tiba Meka Weru tradition is to understand and describe in depth this unique tradition of welcoming guests in Manggarai society, as well as exploring the values contained in it. Data was collected through in-depth interviews with four key informants who come from Manggarai and live in Malang City. The research results show that overall, the Tiba Meka Weru tradition for the Manggarai student community in Malang is an effort to maintain and preserve Manggarai's cultural heritage amidst multicultural campus life. The tradition of